Optimal Redundancy Compensation - Sampson, A. A. (Review of Economic Studies, 1978)
Journal Article Optimal Redundancy Compensation Get access A. A. Sampson A. A. Sampson University of Sheffield and University of New England Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 447–452, https://doi.org/10.2307/2297247 Published: 01 October 1978 Article history Received: 01 December 1976 Accepted: 01 July 1977 Published: 01 October 1978